پاکستان میں متجددانہ رجحانات کا پس منظر:تعارفی مطالعہ: Background of Modern Trends in Pakistan: An Introductory Study - Muhammad Shahbaz; Dr. Muhammad Shahbaz Manj; Riasat Ali (Al-Qamar, 2019)
This article deals with the modern trends in the interpretation of Islamic texts in Pakistan. It argues that the modern interpretation was laid down by Mufti Muhammad Abduh in the Arab world and by Sir Syed Ahmad Khan in Ido-Pak subcontinent. In Indo-Pak subcontinent, Following Sir Syed Ahmad Khan, many other people like Maulvi Chirag Ali, Mumtaz Ali, Syed Amir Ali, Muhammad Ali Lahori, Abdullah Chakralvi, Niaz Fatehpuri, Ghulam Ahmed Parvez etc. adopted the same way of thinking and interpretation. By the literature of such kind of people, modern trends in the interpretation of Islam began to emerge more widely in Pakistan.